Pengaruh penambahan fermentasi ampas kelapa dan dedak halus (padi) dalam pakan terhadap pertumbuhan ikan bandeng (Chanos chanos) - Da Costa, Renaldo; Rebhung, Felix; Sunadji, Sunadji (Nusa Cendana University, 2023)
Research conducted in the period April to June 2022 at the Oesapa Fish Pond Installation, East Nusa Tenggara Province Maritime and Fisheries Service aims to assess the impact of adding fermented coconut dregs and fine bran to milkfish (Chanos chanos) feed. Another objective is to determine the most effective amount of these two ingredients in milkfish feed. This research used a Completely Randomized Design (CRD) method with 4 treatments and was carried out in triplets. The four treatments tested were as follows: Treatments A, B, C and D respectively, namely providing commercial feed with the addition of a mixture of coconut dregs and fine bran at 0, 20, 30 and 40%. Research shows that treatment D, namely providing commercial feed with the addition of a mixture of coconut dregs and fine bran as much as 40%, provides the best results for the growth of milkfish (C. chanos). The absolute weight growth reached 19.29 g, the survival rate reached 100%, indicating that the milkfish in treatment D had an optimal survival rate. Thus, it can be concluded that the addition of coconut dregs and fine bran as much as 40% in fish food is the most effective dose to increase the survival and growth of milkfish (C. chanos) in this study.